2006
DOI: 10.1111/j.1469-7998.2006.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Satellite tracking of Mongolian gazelles (Procapra gutturosa) and habitat shifts in their seasonal ranges

Abstract: Conservation and management are urgently required for Mongolian gazelles Procapra gutturosa inhabiting the Mongolian steppe. We captured and satellitecollared two adult females in Dornogobi Province and two adult females in Omnogobi Province and examined whether their seasonal migration corresponded to shifts in the normalized difference vegetation index (NDVI) in their habitat. The mean NDVI values of their annual, summer and winter ranges were calculated based on data acquired by the moderate-resolution imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 40 publications
2
58
0
1
Order By: Relevance
“…For example, at broader scales, shifts in relative NDVI distribution can explain movement to and from seasonal ranges (e.g. Ito et al 2006). On finer scales NDVI may be used to trace habitat choices of single individuals at a particular movement step (Hebblewhite et al 2008).…”
Section: Scales Of Environmental Change and Animal Movementmentioning
confidence: 99%
“…For example, at broader scales, shifts in relative NDVI distribution can explain movement to and from seasonal ranges (e.g. Ito et al 2006). On finer scales NDVI may be used to trace habitat choices of single individuals at a particular movement step (Hebblewhite et al 2008).…”
Section: Scales Of Environmental Change and Animal Movementmentioning
confidence: 99%
“…For instance, Argos systems and GPS with satellite communication systems have been used to track wild ungulates in Mongolia (Kaczensky et al 2010). We showed that Mongolian gazelles moved distances greater than 300 km (the maximum linear distance between two locations traveled by one individual gazelle in a year) and changed their range seasonally (Ito et al 2006(Ito et al , 2013b. The gazelles moved more than 100 km per week during some periods of the year, whereas the distances moved were short in other periods.…”
Section: Movement Ecology Of Mongolian Gazellesmentioning
confidence: 90%
“…Similarly, during a drought period in September 2005, Olson et al (2009a) reported a mega-herd of more than 200,000 gazelles in areas with a high probability of gazelle occurrence predicted by a NDVI-based model. In the southeastern Gobi, the shifts in NDVI values between the summer and winter ranges explained the gazelles' seasonal movements (Ito et al 2006), and interannual differences in the spatial distribution of NDVI explained the interannual differences in the seasonal range of the tracked gazelles (Ito et al 2013b). The interannual differences in locations were much larger in winter than in summer, likely because of the large differences in the spatial distribution of snow cover.…”
Section: Movement Ecology Of Mongolian Gazellesmentioning
confidence: 99%
See 1 more Smart Citation
“…The NDVI can be used to show spatial and temporal trends in vegetation dynamics, productivity, and distribution, and therefore can be a useful tool to investigate the interaction between vegetation and animal activity, including migration (Ito et al, 2006).…”
Section: Barnacle Geese and Research Problem 121 New Index To Test mentioning
confidence: 99%